2005
DOI: 10.1210/jc.2004-1814
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Endothelial Cell Steroid Receptor Expression and Steroid Effects on Gene Expression

Abstract: Controversy exists regarding the expression of specific steroid receptor proteins and mRNA in human microvascular endometrial endothelial cells (HEECs). Thus, we studied steroid receptor expression in early passaged HEEC cultures and freshly isolated HEECs. Analysis of estrogen receptor (ER) and progesterone receptor (PR) mRNA levels was carried out with real-time quantitative RT-PCR, and the repertoire of genes activated by their respective steroid ligands was assessed by mRNA microarray analyses of 18,400 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…It has also been shown that HEEC has a higher vascular endothelial growth factor (VEGF)-binding capacity than a number of other endothelial cell types such as human coronary endothelial cells, human umbilical vein endothelial cells, and human dermal endothelial cells, suggesting that HEECs are more sensitive to VEGF compared to other endothelial cells. 2 There are several studies in which the expression of sex steroid receptors in HEEC has been investigated, [2][3][4][5][6][7][8] but up to now estrogen receptor b (ER-b) is the only one proven to be present. Results regarding the expression of other steroid receptors are conflicting, but there are some reports that progesterone receptor (PR) is probably present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that HEEC has a higher vascular endothelial growth factor (VEGF)-binding capacity than a number of other endothelial cell types such as human coronary endothelial cells, human umbilical vein endothelial cells, and human dermal endothelial cells, suggesting that HEECs are more sensitive to VEGF compared to other endothelial cells. 2 There are several studies in which the expression of sex steroid receptors in HEEC has been investigated, [2][3][4][5][6][7][8] but up to now estrogen receptor b (ER-b) is the only one proven to be present. Results regarding the expression of other steroid receptors are conflicting, but there are some reports that progesterone receptor (PR) is probably present.…”
Section: Introductionmentioning
confidence: 99%
“…Results regarding the expression of other steroid receptors are conflicting, but there are some reports that progesterone receptor (PR) is probably present. 2,6 Although the regulation of endometrial growth and regression by estrogen and progesterone has been well studied, the direct and indirect roles of these steroids in angiogenesis and in HEECs are not clear. It has been suggested that ovarian steroids are capable of inducing genes involved in endometrial differentiation of human uterine microvascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…A distinctive feature of endometrial endothelial cells of the marmoset was the preferential staining for ERb over PR or ERa at all stages of the cycle and during pregnancy. This phenomenon has been described in women (Critchley et al 2001, Lecce et al 2001) and macaques (Brenner & Slayden 2004), and has been confirmed by studies on human microvascular endometrial endothelial cell (HEEC) cultures (Krikun et al 2005). This suggests a role for oestrogen directly upon endometrial Oestrogen and progesterone receptors in marmoset endothelial cells influencing angiogenesis and vascular permeability.…”
Section: Discussionmentioning
confidence: 61%
“…The principal actions are likely to be on endometrial endothelial cells, mediated by VEGF receptors (Nayak & Brenner 2002, Rowe et al 2003. A link between oestrogen action on endometrial endothelial cells and expression of VEGF, other angiogenic factors or their receptors has yet to be established as addition of oestrogen to HEEC cultures failed to alter their expression levels (Krikun et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a molecular level embryo implantation is a dialog between blastocyst and receptive endometrium which is mediated by various growth factors, cytokines, lipid mediators, transcription factors and other putative molecules often regulated by steroid hormones. In recent years, numerous studies applying global gene expression analysis have found a wide range of genes up-or down regulated in human endometrium during the IW (Carson et al, 2002;Riesewijk et al, 2003;Horcajadas et al, 2004;Krikun et al, 2005;Mirkin et al, 2005;Simon et al, 2005;Punyadeera et al, 2005;Talbi et al, 2006;Haouzi et al, 2009a,b;Altmäe et al, 2010). Each study has brought out candidate genes believed to be crucial in embryo implantation process but the overlap of potential marker genes between different publications has still remained relatively low.…”
Section: Endometrial Gene Expression During the Time Of Embryo Implanmentioning
confidence: 99%